Anxiety and hope: a study about the caregiver overload in the care of patients with stroke - Murayama, Luis Henrique Vallesquino; Meirelles, Havy Alexssander Abrami; Sampaio, Natalie Carlos Ferreira Mello; Moreira, Bruno Zanluqui; Sampaio, Raul Pansardis; Cotrim, Renan Macionil; Bazan, Rodrigo (Revista de Medicina, 2023)
Stroke involves injury to the central nervous system, presenting most frequently as cerebral infarction and intracerebral hemorrhage. It’s an important cause of disability worldwide, being associated with high burden to the patients’ caregivers, who are, frequently, family members. In that matter, it is reported that the main caregivers of stroke patients have the same, or even greater incidence of mental illnesses, such as depression and anxiety. Therefore, we present this study protocol aiming to observe the association between the patient’s type of stroke along with the severity of their sequelae, and the levels of anxiety and hope of their caregivers, in a descriptive, cross-sectional study with a quali-quantitative approach. For that purpose, patients of both sexes, over 18 years of age, who have had a stroke and are being followed up at the Cerebrovascular Diseases Ambulatory will be randomly selected. Then, data will be collected from the caregiver through questionnaires: Zarit Burden Interview (ZBI), Beck Hopelessness Scale (BHS), Beck Anxiety Inventory (BAI) and a socioeconomic questionnaire. The ZBI analyzes psychological, financial, social and physical aspects of the caregiver’s universe, while the BAI and BHS are used to quantify the caregiver’s anxiety state, and bring information about the individual’s hope and life expectations. Information about the patient will be obtained from medical records. Finally, we hope to find useful information for health services about the reality in which they are inserted, in order to promote the creation of disease prevention measures, which is essential to improve the quality of healthcare provided.